PEMBERDAYAAN MASYARAKAT DESA MELALUI PROGRAM KULIAH KERJA NYATA (KUKERTA) UNIVERSITAS KADIRI DI KECAMATAN NGASEM KABUPATEN KEDIRI - Erik Irham Lutfi; Budi Heryanto; Hendy; M. Dian Ruhamak; Ema Fatmawati Anindya; Agus Sugeng Rahayu (Jurnal Abdi Masyarakat, 2025)
Universities play a strategic role in supporting community development through the implementation of the Tri Dharma of Higher Education, particularly community service. One form of this implementation is the Community Service Program (Kuliah Kerja Nyata/KUKERTA). The 2025 KUKERTA Program of Universitas Kadiri was conducted in Ngasem District, Kediri Regency, an area with considerable local resource potential that still requires assistance in the fields of literacy, law, and social community development. The KUKERTA program was carried out in August 2025 in four villages using methods of observation, program planning, activity implementation, as well as evaluation and reporting. The community service activities focused on three main programs: Literacy Transformation, POSBANKUM (Legal Aid Post), and participation in the commemoration of the Independence Day of the Republic of Indonesia. The Literacy Transformation Program aimed to improve community literacy culture through strengthening reading and writing literacy, digital literacy, financial literacy, and health literacy, as well as establishing village reading corners. The POSBANKUM program was directed at improving public access to and understanding of legal services through legal consultation and counseling. KUKERTA students also actively participated in the commemoration of Indonesia’s Independence Day as a form of social engagement and to strengthen the values of nationalism, mutual cooperation, and community solidarity in rural areas. The implementation of the KUKERTA program is expected to provide positive and sustainable impacts for the community while serving as a learning platform for students to develop social, leadership, and community service competencies.